Detection of a circulating form of vascular cell adhesion molecule-1: raised levels in rheumatoid arthritis and systemic lupus erythematosus. - Wellicome, S M (1993)
We have developed a panel of MoAbs against four separate but overlapping epitopes on endothelial cell (EC) vascular cell adhesion molecule-1 (VCAM-1). Two of the MoAbs (1G11 and 1E5) inhibited T cell adhesion to tumour necrosis factor (TNF)-activated EC, whilst two MoAbs (1.4C3 and 6D9) did not. Using these MoAbs we have identified a circulating form of VCAM-1 (cVCAM-1) which has identical epitope distribution to the EC form, and which is able to support the adhesion of the human lymphoblastoid cell line Jurkat J6 by a VLA-4- and VCAM-1-dependent mechanism when immobilized from plasma. cVCAM-1 isolated by immunoaffinity and size-exclusion chromatographies was shown by SDS-PAGE to have an apparent mol. wt of 85-90 kD. Levels of cVCAM-1 were significantly raised (P < 0.001) in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) compared with normal individuals. It is possible that cVCAM-1 may be a useful plasma marker for the diagnosis and management of patients with inflammatory diseases. Furthermore, detection of elevated cVCAM-1 levels may act as a guide to the importance of VCAM-1-dependent cell adhesion in different pathological settings.